Effect of ZnO additions on the magnetic behaviour in YBCO superconductors - Çelebi, S.; Kölemen, U.; Malik, A.I.; Öztürk, A. (Wiley, 2002)
We have investigated the effect of ZnO additions on YBCO prepared by conventional solid state reaction method by ac susceptibility measurements. We measured the ac susceptibility of sintered YBCO pellets as a function of temperature and ac magnetic field amplitude. The superconducting transition temperatures and critical current density depend on the Zn content of the samples. The intergrain critical current density was increased significantly by 1 wt% of ZnO compared to that of undoped samples. This conclusion was drawn by various aspects. The values of the extrapolated jcm(0) are 160, 308 and 1000 A/cm2 for samples S1, S2, and S3 respectively. We also qualitatively discuss experimental results in the framework of the Bean critical state model, estimate the effective volume fraction of the grains and determine the temperature dependence of the critical current density by means of the best fit of the calculated data for the experimental matrix susceptibility.